Evaluation of a well-being campaign following a natural disaster in Christchurch, New Zealand. Issue 4 (7th August 2016) - Calder, Kristi; D'Aeth, Lucy; Turner, Sue; Fox, Ciaran; Begg, Annabel
Abstract: The All Right? campaign, was developed as an over-arching mental health promotion campaign following the 2010-2011 earthquake sequence (Christchurch, New Zealand). To our knowledge this campaign is unique in promoting population wide psychosocial well-being following a disaster. Mixed methods were used for data collection. The campaign has achieved a wide reach within the affected population (70%) and high levels of agreement from those surveyed who were aware of the campaign that the messages were helpful (84%). Success factors included: strong relationships between key agencies prior to a disaster, local research to inform the use of appropriate language for translating evidence based well-being messages into a local setting, not being marketed as a government message whilst maintaining strong relationships with key agencies. In addition to the mass appeal of the All Right? campaign, targeted campaigns from the inception would have been beneficial, in particular, to reach Māori and Pacific communities. As a result of the evaluation findings, this more specifically focused messaging has been developed. There would be value in the replication of the campaign particularly in the post disaster context in other high income countries, this would need to be tailored on the basis of local research and need.